Relationship of Inflammatory Mediators and Sex-Related Parameters in Jordanian Adult Men Patients with COVID-19 - I. Al-Bashiti, Amneh; Ahmed, Dr. Khaled; M. Alqaisi, Khalid (Journal of Medical Biochemistry, 2022)
Background: Recent epidemiological data suggest that Coronavirus disease 2019 (COVID-19) has a gender predisposition, with men being more seriously affected than women and older men accounting for the majority of deaths. Therefore, this study aimed to investigate the serum testosterone, inhibin B, intrleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) levels in different age groups of Jordanian males with SARS-CoV2 infection and to evaluate the correlation of these markers in male patients with COVID-19.Methods: This study was performed on 157 selected individuals divided into two groups; COVID-19 patients and healthy controls. The participants of each group were further divided into two subgroups based on the age (20-50 years and 51-80 years age groups). The biochemical tests that are included in this research are testosterone, inhibin-B, TNF-α, and IL-6 using standard techniques according to the manufacturer's instructionsResults: The levels of IL-6 were significantly higher in COVID-19 patients than healthy individuals (7.63 ± 6.30 vs. 5.54 ± 2.10, P=0.006). Similarly, the difference between the levels of TNF-α in the study groups were statistically significant (P=0.001). The mean testosterone levels in COVID-19 patients and healthy controls were 1.53 ± 1.24 and 3.87 ± 1.44, respectively (P < 0.001), whereas the mean inhibin B levels in COVID-19 patients (54.29 ± 7.33) were lower than  in healthy controls (64.14 ± 37.66) with P = 0.011. TNF-α was significantly and positively correlated with age (r =  0.263, P = 0.018) and IL-6 (r = 0.245, P = 0.027). Inhibin B had a significantly, but negatively correlation with TNF-α (r = −0.326, P = 0.003).Conclusions: It can be concluded that most men seeking medical attention with symptomatic COVID-19 had low testosterone and inhibin B levels with increased both IL-6 and TNF-α, which are independent of age conforming the deleterious effects of SARS-CoV-2 infection on testicular function and immune response induction.